2015
DOI: 10.1111/jfpp.12692
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Volatile Profiles and Odor Activity Values of Turkish Coffee and French Press Coffee

Abstract: Volatile compositions of coffee obtained from two different coffee brewing methods, Turkish coffee (TC) and French press coffee (FPC), were analyzed by the gas chromatography-mass spectrometry technique. Liquid-liquid extraction with dichloromethane was used for extraction of volatile compounds. A total of 60 and 58 volatile compounds comprising furans, lactones, phenolic compounds, pyridines, pyrazines, acids, cyclopentenes, pyrroles, furanones, ketones, alcohols, aldehydes and thiols were identified and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 36 publications
4
36
0
Order By: Relevance
“…Thirteen chemical classes were observed, including 6 alcohols, 5 aldehydes, one carboxylic acid, 3 esters, 17 furans, one furanone, 13 ketones, 2 oxazoles, 4 phenolic compounds, 14 pyrazines, one pyridine, 8 pyrroles and 3 sulfur-containing compounds. These compounds have also been reported by several research groups that analyzed coffee with HS GCMS [11,17,[19][20][21]. The major compounds found in both sets of coffee samples were acetone, methylpyrazine, furfural, 5-methylfurfural and 2-furanmethanol.…”
Section: Gcms Analysis Of Coffee Brew Samples and Compound Identificsupporting
confidence: 75%
See 1 more Smart Citation
“…Thirteen chemical classes were observed, including 6 alcohols, 5 aldehydes, one carboxylic acid, 3 esters, 17 furans, one furanone, 13 ketones, 2 oxazoles, 4 phenolic compounds, 14 pyrazines, one pyridine, 8 pyrroles and 3 sulfur-containing compounds. These compounds have also been reported by several research groups that analyzed coffee with HS GCMS [11,17,[19][20][21]. The major compounds found in both sets of coffee samples were acetone, methylpyrazine, furfural, 5-methylfurfural and 2-furanmethanol.…”
Section: Gcms Analysis Of Coffee Brew Samples and Compound Identificsupporting
confidence: 75%
“…Gas chromatographymass spectrometry (GCMS) is a powerful analytical technique that is widely used to profile volatile compounds in coffee because it can efficiently separate and identify compounds [11,12,[18][19][20][21]. Coffee samples can be prepared by a solvent extraction method followed by direct liquid injection into the GC column, allowing the detection of volatile and semi-volatile compounds in coffee [12,17,22,23]. However, some volatile compounds may be lost during the sample preparation step.…”
mentioning
confidence: 99%
“…CV (%) coefficient of variation, LSD (P < 0.05) least significant difference at P value less than 0.05 a Summarized bySunarharum et al (2014) b Summarized byAmanpour et al (2015) c Summarized byPiccino et al (2014) d Summarized byBelitz et al (2009) …”
mentioning
confidence: 97%
“…After boiling water (TC), immersion (FPC), and pressurized brewed coffees, there is another kind of beverage called lungho or lungo coffee, characterized as a mild beverage with a large volume (100 to 125 mL), which is usually consumed in combination with milk and/or cream. Whereas espresso coffees are intense coffee beverages with a low extract volume (25 to 30 mL) usually extracted from fine grinds, some lungo beverages can also be extracted in the espresso fashion, but their sensory and quality characteristics definitely differ from those of espresso (Amanpour & Selli, ).…”
Section: Primary Processingmentioning
confidence: 99%
“…Sensory evaluation of all extraction methods also found that SE and AE have the most desireable texture/body, aroma and flavor profile, astringency, and so on, whereas filter and KK coffee are poorest for all these quality attributes (Gloess et al., ). Recently, Amanpour and Selli () differentiated well between boiled (that is, TC) and immersion (that is, FPC) coffees which are different on the basis of their brewing/extraction techniques. These different extraction techniques not only bring about changes in the volatile profile of the 2 coffees but also bring about variations in the odor activity values (OAV) of 13 selected maker volatiles.…”
Section: Primary Processingmentioning
confidence: 99%